MY BOOK OF The Elements - Dingle, Adrian (London : Dorling Kindersley Limited, 2024)
"My book of the elements" is a wonderful introduction to the periodic table. Covering all the elements, from the unreactive to the radioactive, as well as key science topics, such as states of matter, this visual book is something that every young science enthusiast will want to own. It is a source of information you can trust, one that is age-appropriate and supports your child's schoolwork. From Hydrogen to Oganesson, each element is explored in detail, with information on properties and use cases, as well as fun facts.
Includes index.
Keywords: Periodic table of the elements -- Juvenile literature; Chemical elements -- Juvenile literature; Chemistry -- Juvenile literature